An Assistance to the Dokdak Village Karang Taruna Group in Managing the Karya Village Website - Suryana, Aan; Pajriah, Sri (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
Managing the blacksmith's village website is an important aspect of developing the potential that exists in Dokdak Village which so far has not been conveyed to the wider community. The lack of knowledge of the community, especially the Youth Organization group, is one of the causes. Based on this, website management assistance activities were carried out for the Karang Taruna group. This mentoring activity used various lecture methods, demonstrations, and exercises, with steps to identify needs, develop training materials, train, create website management plans, direct mentoring, monitoring and evaluation, content development and promotion, technical maintenance, and continued empowerment. There were 7 participants in the mentoring activities. This mentoring activity was aimed at analyzing the role of the Dokdak Village youth group in managing the Dokdak Blacksmith Village website, thereby strengthening their involvement in managing and maintaining the Blacksmith Village website. The results of the mentoring activities showed that the Dokdak Village Karang Taruna group could be more active and have a better understanding of managing the Blacksmith Village website. They could collect, organize, and publish local information effectively. From this explanation, it could be concluded that the assistance of the Dokdak Village youth group in managing the website could be a reference for the local government and related parties to develop the potential that exists in their environment by continuing to encourage community involvement.